Progress Update on STING Agonists as Vaccine Adjuvants - Yanru Shen; Weijin Huang; Jianhui Nie; Li Zhang (Vaccines)
Low antigen immunogenicity poses a significant challenge in vaccine development, often leading to inadequate immune responses and reduced vaccine efficacy. Therefore, the discovery of potent immune-enhancing adjuvants is crucial. STING (stimulator of interferon genes) agonists are a promising class of adjuvants which have been identified in various immune cells and are activated in response to DNA fragments, triggering a broad range of type-I interferon-dependent immune responses. Integrating STING agonists with vaccine components is an ideal strategy to bolster vaccine-induced immunity to infections and cancer cells. Several STING agonists are currently under investigation in preclinical studies and clinical trials; however, some have shown limited efficacy, while others exhibit off-target effects. To ensure safety, they are typically delivered with carriers that exhibit high biocompatibility and insolubility. In this review, we present the latest research on natural and synthetic STING agonists that have been effectively used in vaccine development, and summarize their application in adjuvant preventive and therapeutic vaccines. Additionally, we discuss the safety of STING agonists as vaccine adjuvants by reviewing potential delivery strategies. Overall, incorporating STING agonists into vaccine formulations represents a significant advancement in vaccine research with the potential to significantly enhance immune responses and improve vaccine efficacy. However, ongoing research is still required to identify the most effective and safe delivery strategies for STING agonists, as well as to evaluate their long-term safety and efficacy in clinical trials.